Providing an Ethical Marketing Model for Non-Profit Universities in Iraq - Mohsin, Haider Kifah.; Shirkhodaie, Meysam; sani, Mohsen Alizadeh; Abedin, Bahareh (Journal of Ecohumanism, 2024)
In the contemporary business environment, managers face ethical challenges that require making decisions that go beyond traditional operational considerations to include principles of rightness and ethics. Marketing is one of the most vulnerable areas to ethical abuses in organizations, as it represents an interactive interface that brings together customers and other stakeholders. Studying marketing ethics requires a multidimensional approach that includes individual, organizational, and social aspects. Accordingly, this research aims to develop an ethical marketing model that is suitable for non-profit universities in Iraq. The study included professors and experts from non-profit universities in Iraq as a statistical community. 215 samples were collected using the available non-probability method. The results showed that the ethical marketing mix is affected by several main factors such as increased social awareness, societal demand, competition in the education market, and legal and regulatory pressures. This research contributes to building a practical framework for ethical marketing in the context of non-profit universities in Iraq, which enhances their marketing strategies and their social and educational role. The results of structural equation modeling using Smart PLS program indicate confirmation of most of the relationships proposed in the research model. The study showed that adopting ethical marketing, taking into account the economic, cultural, political and social conditions in Iraq, represents a strategic option to support non-profit universities, ensure their sustainability and enhance their competitiveness. The results of this research show the importance of scientific planning and efficient resource management to ensure the success of non-profit universities and enhance their educational and social mission.